Status of Fish Consumption in Kolhapur City - Parakhe3, M. P. Bhilave3, R. A. Jamdade1*, V. Y. Deshpande2, Y. B. (Recent Research in Science and Technology, 2011)
The survey was conducted during the period of 2009-10 at various regions of Kolhapur city through personal interviews (549) to access region specific consumption rates by targeting the residence of the respondent. The relevant questions were asked to know knowledge of the respondents of a particular population [3]. The purpose of the survey was to study consumer attitude towards fish consumption that can be currently determined by parameters such as price, taste, quality, availability or hygiene at point of sale. In order to satisfy increasing demands many marketing strategies could be evolved and, simultaneously, help could be offered for the development and management of fisheries.